Unlocking the microbial aerobic denitrification potential in reservoirs and lakes: Development of a novel aerobic denitrifying fungal medium and its practical application - Haihan Zhang; Lunpei Chen; Ben Ma; Xiang Liu; Xiaoyan Liu; Fengrui Li; Min Fu; Tinglin Huang; Kang Wang; Guoqiang Xi; Boris Adamovich; Dmitry B. Kosolapov (Water Research, 2026)

Dynamics of global CO2 and PM2.5 nexus and suggestions on the pathway heading to sustainable development for different income countries - Jiaxin Liu; Ben Fu; Lijian Han; Guixiang Jin; Yuhui Xiao; Keqing Chen; Weifeng Li; Weiqi Zhou; Yuguo Qian (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Development of a frequency-domain wave load mapping methodology and its initial application to a 15 MW semi-submersible floating wind turbine - Shuijin Li; Rutian Wan; Yichao Lv; Ling Wan; Jie Fu; Ben He; Yulong Li; Torgeir Moan (Ocean Engineering, 2026)

An adaptive two-grid preconditioner and linearly implicit scheme for shale gas transport in fractured porous media - Maria Vasilyeva; Ben S. Southworth; Shubin Fu (Computational Geosciences, 2026)
We consider a nonlinear mixed-dimensional model for simulating gas transport in shale formation. The mathematical model consists of a coupled system of nonlinear equations, where flow within fractures is represented using a lower-dimensional representation. For the numerical solution of the coupled transport problem, we construct an unstructured mesh that resolves lower dimensional fractures on the grid level and use the finite element approximation to build a discrete system. To construct an efficient scheme for the resulting nonlinear problem, we use an explicit-implicit method for time integration, where we carefully choose an additive partition of the nonlinear operators to separate the stiff linear component and integrate it implicitly to ensure the stability of the time integration. Next, we invert the linear partition of the operator by constructing an efficient two-grid preconditioner for shale gas transport in fractured porous media. We use a local pointwise smoother on the fine grid and carefully design an adaptive multiscale space for coarse grid approximation based on local generalized eigenvalue problems. We utilize an adaptive thresholding to automatically identify local dominant modes which correspond to the very small eigenvalues in local domains. We remark that such spatial features are automatically captured through our local spectral problems, and connect these to fracture information in the global formulation of the problem. Approximation properties of the local spectral space with convergence of the proposed two-grid algorithm are given. Numerical results are presented for two-dimensional fracture distributions with 30 and 160 fractures and a three-dimensional test case with 30 fractures, demonstrating iterative convergence independently of the contrast of fracture and porous matrix permeability.

Failure Behavior of Deep Tunnels Subjected to TBM-Induced Dynamic Disturbance - Hong-Yuan Fu; Ben-Guo He; Si-Yuan Dou (Rock Mechanics and Rock Engineering, 2026)

Failure characteristics and development mechanism of time-delayed rockburst in a tunnel excavated via the drilling and blasting method: A case study - Lei Hu; Wen-Fei Chang; Ben-Guo He; Wei Zhang; Jun Zhao; Zhi-Bin Yao; Meng-Fei Jiang; Hong-Pu Li; Lian-Jie Fu (Tunnelling and Underground Space Technology, 2026)

A regional hydrodynamic coefficient reconstruction workflow for internal-load recovery of a 15 MW semi-submersible floating wind turbine - Shuijin Li; Shuaibing Zhang; Ling Wan; Jie Fu; Ben He; Yibo Wang (Ocean Engineering, 2026)

Molecular mechanisms underlying the maintenance of protein homeostasis in pearl gentian grouper under acute high-temperature stress - Qiu-Ting Yang; Ren-Xie Wu; Yan-Shan Liang; Ben-Ben Miao; Su-Fang Niu; Feng-Ling Lei; Fan-Li Long; Zhen-Bang Liang; Yu-Xin Shen; Yu Fu (Journal of Thermal Biology, 2026)

Water lifting aerators control algal growth in drinking water reservoirs: Performance, mechanism and application - Min Fu; Yue Xu; Xiang Liu; Tinglin Huang; Ben Ma; Fengrui Li; Wanting Shi; Haihan Zhang (Water Research, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Synergistic Al@MgH2 composites for on-demand power generation in fuel cells - Yu Xiong; Wenshang Chen; Lizhong Duan; Huihu Wang; Shenghao Jiang; Chenhuinan Wei; Xing Xiang; Yun Zhao; Qianyu Wang; Xudong Fu; Ben Chen (Chemical Engineering Journal, 2026)

Amplification and attenuation mechanisms of blast-induced vibration adjacent to cross passage in deep tunnels - Yu Lu; Ben-Guo He; Qi Li; Hongyuan Fu (Transportation Geotechnics, 2026)

An interpretable machine learning model for predicting p-y curves of monopiles in clay - Biao Li; Wen-Gang Qi; Yi-Fa Wang; Fu-Ping Gao; Lu Jing; Shun-Yi Wang; Ben He (Ocean Engineering, 2026)

The construction of marine protected areas in China—Legal Dilemma, challenges and suggestions - Yen-Chiang Chang; Ben-chao Fu; Chingyu Huang; Jinhua Guo (Journal for Nature Conservation, 2026)

Strengthening Connections in Observing the North Atlantic Meridional Overturning Circulation: Outcomes from a Joint RAPID-OSNAP Workshop - Nicholas Foukal; Isabela Le Bras; Yao Fu; Tillys Petit; Tiago Biló; Shane Elipot; Ben Moat (Oceanography, 2026)
The Atlantic Meridional Overturning Circulation (AMOC) redistributes heat, salt, oxygen, carbon, and nutrients in the Atlantic Ocean, providing warmth and moisture to the climate of northern Europe (Rhines and Häkkinen, 2003), displacing the Intertropical Convergence Zone northward of the equator (Ben-Yami et al., 2024), sequestering anthropogenic carbon in the deep ocean (Brown et al., 2021), and seeding the subpolar North Atlantic with sufficient nutrients to support the annual spring phytoplankton bloom (Williams et al., 2026). While models and proxies of the AMOC have been instrumental in understanding its past and future variability, large inter-model differences necessitate direct observations to provide a baseline from which to compare the models, as well as an unambiguous time series of recent AMOC variability. However, measuring a system as large and complex as the AMOC presents many challenges: spanning thousands of kilometers horizontally and covering full ocean depths, the AMOC is composed of currents that vary on daily to millennial time scales. Recirculating flows that can be an order of magnitude stronger than the AMOC itself further complicate observations.

Androgen induces 3′UTR shortening of de novo lipogenesis genes by alternative polyadenylation in prostate cancer cells - Wei-Jie Sun; Fei Liang; Hui Zhao; Yun-Mei Wang; Zhong-Yin Zhou; Hui Xu; Hang Liu; Dong Tang; An-Long Xu; Yong-Gui Fu; Xi Li; Jun Ouyang; et al. (Science China Life Sciences, 2025)
Alternative polyadenylation (APA) is a pervasive mechanism that is emerging as a formidable player in post-transcriptional regulation. The transcriptional landscape can be altered via APA in response to various stimulating factors. Using the PacBio single-molecule long-read sequencing method, we present for the first time the 3′UTR landscape and reveal a global increase of APA events in prostate cancer (PCa) LNCaP cells in response to androgen dihydrotestosterone (DHT), a critical regulator of PCa progression. With evidence from differential gene expression analyses of Illumina RNA-sequencing data, we demonstrated that genes with DHT-induced changes in both expression and APA were enriched in lipid metabolism. These genes predominantly supported de novo fatty acid synthesis, such as FASN and ACSL3 . Furthermore, we showed that an isoform switch to the proximal poly(A) site of these genes depended on the androgen receptor, and the expression of cancer-associated genes was upregulated by the escape of miRNA-regulated repression machinery. To address the role of key gene shortening in PCa, we prepared 22RV1-FS cells missing the distal poly(A) signal of FASN in the AR + PCa cell line 22RV1 using CRISPR/Cas9 technology. As expected, the edited 22RV1-FS cells overexpressed FASN mRNA and protein and were inclined to cell proliferation in vitro and tumorigenesis in vivo . Interestingly, we found that FASN transcripts with a shortened 3′UTR were significantly increased in advanced PCa and castration-resistant prostate cancer compared with benign prostate hyperplasia, suggesting a possible association between usage of the proximal poly(A) site and disease progression. Therefore, our study highlights the importance of the APA mechanism in response to DHT stimulation in PCa cells and provides a novel regulatory mechanism through which DHT-induced APA causes altered expression of de novo lipogenesis genes, with a possible association with the progression of PCa.

An effective design method of high-strength steel columns with limited datasets using physics-guided conditional tabular GAN - Ben Mou; Hong Chen; Yuguang Fu (Engineering Structures, 2025)

Daylight glare index modification for inhomogeneous semitransparent photovoltaic windows: Based on subjective surveys and objective experiments - Lu Yang; Jinqing Peng; Ganhua Fu; Yutong Tan; Ben Wu (Energy and Buildings, 2025)

Decoding taste & odor - producing actinobacteria in drinking water reservoir sediments: Community distribution and carbon metabolic preferences - Xiang Liu; Tingting Pei; Tinglin Huang; Danhong Yang; Min Fu; Shengzhao Jing; Ben Ma; Xiaoyan Liu; Jianchao Shi; XinJian Niu; Hongbin Sang; Haihan Zhang (Journal of Water Process Engineering, 2025)

Increasing susceptibility of vegetation productivity to compound drought from 2001 to 2020 - Jiwang Tang; Ben Niu; Zhigang Hu; Gang Fu; Xianzhou Zhang (Global and Planetary Change, 2025)

China’s marine plastic pollution governance path: focusing on the judicial positioning of PIL initiated by procuratorial agencies - Ben-Chao Fu; Chuan-Kai Guo; Xiu-Juan Li; Hai-Dong Cai; Jin-Hua Guo; He-Ran Li (Frontiers in Marine Science, 2025)
Can procuratorial agencies play a key role in China’s governance of marine plastic pollution (MPPG)? Within the current discussions about the legal framework of China’s MPPG, courts, marine environmental regulatory authorities, procuratorial agencies, and environmental protection organizations are typically seen as the main stakeholders. However, the role of procuratorial agencies, as the statutory entity for initiating PIL in marine environmental protection, has been significantly overlooked. This raises a range of questions including how should procuratorial agencies leverage their advantages in PIL to enhance the diversity of participants in the litigation process? What inherent challenges exist in marine environmental lawsuits? What substantive and procedural obstacles will procuratorial agencies face when engaging in MPPG-related litigation? This study argues that procuratorial agencies, by fulfilling their public interest litigation (PIL) function in marine environmental protection, can effectively improve MPPG governance. The study focuses on issues such as the unclear prerequisites for initiating MPPG-related lawsuits by procuratorial agencies, the criteria for selecting diverse litigation models, and the applicability of procuratorial agencies’ PIL in foreign-related cases.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Dynamic covalent synthesis of highly-crystalline and fully-cyclized aromatic COF as an artificial interphase layer toward stable lithium metal batteries - Wei Shao; Da Xu; Tiantian Wang; Huanghao Pan; Ying Liu; Xue Gao; Jiahuan Luo; Jing Wang; Zhong-Kun Li; Yao Guo; Huihui Zhao; Ning Fu; et al. (Chemical Engineering Journal, 2025)

Model test study on electro-osmotic dry tailings dams of conductive grids - Changbo Du; Xinqi Jiang; Fu Yi; Ben Niu; Juyu Jiang (Process Safety and Environmental Protection, 2025)

Experimental investigation of scour effects on regular and breaking wave loads on a monopile - Biao Li; Wen-Gang Qi; Fu-Ping Gao; Ben He; Li-Jing Yang (Coastal Engineering, 2025)

Corrigendum to “Shifted trend in drought sensitivity of vegetation productivity from 1982 to 2020” [Agricultural and Forest Meteorology 362 (2024) 1-10/110388] - Jiwang Tang; Ben Niu; Gang Fu; Jinlong Peng; Zhigang Hu; Xianzhou Zhang (Agricultural and Forest Meteorology, 2025)

Global Soil Methane Uptake Estimated by Scaling Up Local Measurements - Jiawei Jiang; Zhifeng Yan; Jinshi Jian; Shushi Peng; Hanqin Tian; Kendalynn A. Morris; Robert M. Ellam; Jesper Riis Christiansen; Huai Chen; Jianzhi Dong; Si‐Liang Li; Pingqing Fu; et al. (Global Change Biology, 2025)
Aerobic soils remove methane from the atmosphere, but global soil methane uptake (SMU) estimates remain highly uncertain due to challenges in scaling local data. We develop a data‐driven approach to refine this global estimate by incorporating local data of 79,800 flux measurements from 198 sites. This novel approach links the global SMU budget to local SMU fluxes by varying its parameters with soil properties. Our 2003–2018 global SMU estimate is ~39.0 Tg CH 4 year −1 —about 30% higher than existing bottom‐up estimates and consistent with top‐down assessments. Cold grasslands and deserts were found to contribute nearly 30% of the total SMU, while disturbed agricultural biomes have the lowest SMU. The projected future global SMU is shaped by temperature and atmospheric methane, though local SMU is primarily influenced by changes in soil moisture. This study emphasizes the potential of soils in climate regulation and highlights the need to focus on key biomes for a better understanding of the soil‐atmosphere methane feedback and optimizing methane management strategies.

Shifted trend in drought sensitivity of vegetation productivity from 1982 to 2020 - Jiwang Tang; Ben Niu; Gang Fu; Jinlong Peng; Zhigang Hu; Xianzhou Zhang (Agricultural and Forest Meteorology, 2025)

Stable aryl-armed dihydrophenazines-based radicals - Lu Liu; Yuxuan Li; Haichang Fu; Xuecheng Guo; Qing Wan; Weijun Li; Ben Zhong Tang; Zhiming Wang (Chemical Engineering Journal, 2024)

Electroosmosis of gold tailings under multiple electrokinetic geosynthetics electrodes - Changbo Du; Ben Niu; Fu Yi; Meng Wang; Xinqi Jiang (Geotextiles and Geomembranes, 2024)

PROSAC as a selection tool for SO-PLS regression: A strategy for multi-block data fusion - Jose A. Diaz-Olivares; Ryad Bendoula; Wouter Saeys; Maxime Ryckewaert; Ines Adriaens; Xinyue Fu; Matti Pastell; Jean-Michel Roger; Ben Aernouts (Analytica Chimica Acta, 2024)

Modelling the dynamic gas/particle partitioning process of semi-volatile organic compounds emitted from point sources: Quantitative analysis and impact assessment - Fu-Jie Zhu; Li-Fu Wang; Long-Ze Qu; Wan-Li Ma; Geng-Bo Ren; Ben-Hang Li; Xiao-Dong Ma (Science of The Total Environment, 2024)

Tomato NAC transcription factor NOR-like1 positively regulates tomato fruit softening - Zhen-Zhen Peng; Hong-Li Li; Gang-Shuai Liu; Xiao Su; Xiaodan Zhao; Donald Grierson; Lan-Ting Xiang; Jian-Lin He; Gui-Qin Qu; Hong-Liang Zhu; Ben-Zhong Zhu; Yun-Bo Luo; et al. (Postharvest Biology and Technology, 2024)

Time development of clear-water scour around a pile foundation: Phenomenological theory of turbulence-based approach - Shun-Yi Wang; Wen-Gang Qi; Fu-Ping Gao; Biao Li; Ben He (Coastal Engineering, 2024)

Foraging behavior and sea ice-dependent factors affecting the bioaccumulation of mercury in Antarctic coastal waters - Lin Yang; Ben Yu; Hongwei Liu; Xiaomeng Ji; Cailing Xiao; Mengxi Cao; Jianjie Fu; Qinghua Zhang; Ligang Hu; Yongguang Yin; Jianbo Shi; Guibin Jiang (Science of The Total Environment, 2024)

Response of plant diversity and soil microbial diversity to warming and increased precipitation in alpine grasslands on the Qinghai-Xizang Plateau – A review - Ben Niu; Gang Fu (Science of The Total Environment, 2024)

Outdoor artificial light at night and male sperm quality: A retrospective cohort study in China - Run Tian; Tingting Yang; Chenghan Xiao; Fuping Li; Leyao Fu; Lu Zhang; Jiarui Cai; Sixuan Zeng; Junhao Liao; Guishuang Song; Chuan Yu; Ben Zhang; et al. (Environmental Pollution, 2024)

Simvastatin ameliorates synaptic plasticity impairment in chronic mild stress-induced depressed mice by modulating hippocampal NMDA receptor - Xu-Ben Yu; Kai-Long Zhong; Chuang Chen; Jing Fu; Fang Chen; Hong-Min Zhou; Xiu-Hua Zhang; Kwonseop Kim; Jing-Ye Pan (Psychopharmacology, 2024)

Spatially heterogeneous shifts in vegetation phenology induced by climate change threaten the integrity of the avian migration network - Jie Wei; Fei Xu; Ella F. Cole; Ben C. Sheldon; Willem F. de Boer; Ben Wielstra; Haohuan Fu; Peng Gong; Yali Si (Global Change Biology, 2024)
Phenological responses to climate change frequently vary among trophic levels, which can result in increasing asynchrony between the peak energy requirements of consumers and the availability of resources. Migratory birds use multiple habitats with seasonal food resources along migration flyways. Spatially heterogeneous climate change could cause the phenology of food availability along the migration flyway to become desynchronized. Such heterogeneous shifts in food phenology could pose a challenge to migratory birds by reducing their opportunity for food availability along the migration path and consequently influencing their survival and reproduction. We develop a novel graph‐based approach to quantify this problem and deploy it to evaluate the condition of the heterogeneous shifts in vegetation phenology for 16 migratory herbivorous waterfowl species in Asia. We show that climate change‐induced heterogeneous shifts in vegetation phenology could cause a 12% loss of migration network integrity on average across all study species. Species that winter at relatively lower latitudes are subjected to a higher loss of integrity in their migration network. These findings highlight the susceptibility of migratory species to climate change. Our proposed methodological framework could be applied to migratory species in general to yield an accurate assessment of the exposure under climate change and help to identify actions for biodiversity conservation in the face of climate‐related risks.

Bimetallic Fe-Mn loaded H-ZSM-5 zeolites for excellent VOCs catalytic oxidation at low-temperatures: Synergistic effects and catalytic mechanisms - Wissem Ben Soltan; Jianbiao Peng; Zhiguo Cao; Zheng Fu; Haijin Liu (Chemical Engineering Journal, 2023)

Contribution of HIF-1α to Heat Shock Response by Transcriptional Regulation of HSF1/HSP70 Signaling Pathway in Pacific Oyster, Crassostrea gigas - Huiru Fu; Yongjing Li; Jing Tian; Ben Yang; Yin Li; Qi Li; Shikai Liu (Marine Biotechnology, 2023)

Novel protection systems for the improvement in soil and water stability of expansive soil slopes - Shao-kun Ma; Ben-fu He; Min Ma; Zhen Huang; Sheng-jia Chen; Huan Yue (Journal of Mountain Science, 2023)

Non-uniform thermal characteristics investigation of three-dimensional electrochemical-thermal coupled model for pouch lithium-ion battery - Xiang-Wei Lin; Zhi-Fu Zhou; Xin-Gang Zhu; Bin Chen; Hai Zhu; Ning-Yu Ben; Xu-Dong Wang; Wen-Wei Xu (Journal of Cleaner Production, 2023)

Purifying Metallurgical-Grade Silicon to 4N with 3D Porous Structure by Integrated Metallurgy-Materials Phase Separation - Jian Song; Yifan Liu; Shixiong Mei; Ben Xiang; Jijiang Fu; Siguang Guo; Weili An; Xuming Zhang; Biao Gao; Paul K Chu; Kaifu Huo (Chemical Engineering Journal, 2023)

Legal advice on the Chinese compensatory fund system for oil pollution damage caused by ships from the perspective of marine environmental governance - Ben-Chao Fu; He-Ran Li (Frontiers in Marine Science, 2023)
As one of the primary obstructive factors for marine environmental governance, the frequent occurrence of oil pollution damage caused by ships has resulted in the establishment of compensation funds, such as the Oil Spill Liability Trust Fund of the United States, Ship Oil Pollution Fund of Canada and International Oil Pollution Compensation Fund (IOPC). Frequently suffering from marine oil pollution, China has extended considerable effort in marine environmental governance. Following the introduction of the ‘green principle’ into the Civil Code, China attached increasing significance to the legislation including compensation for oil pollution damage caused by ships. China formally established a compensation fund in 2012, and the past decade has witnessed the burgeoning development of the Chinese Ship-source Oil Pollution Compensation Fund (CSOPC), in addition to several defects which impede the fund from achieving the goal of marine environmental governance. As a national fund that is independent of the IOPC, the CSOPC adopts several regulations that are distinctive from internationally recognized practice; for instance, not recognizing pure economic loss within the scope of compensation. Such unique parameters, though partially originating from the national conditions in China, have resulted in glaring defects, including incomplete compensation scope and inappropriate compensation measures. Given the above problems, this study endeavours to provide several legal recommendations from the perspective of macro policies for improving the top-level design of the system, enhancing oil pollution compensation capabilities, and promoting the internationalization process. The study proposes two potential regulatory paths for innovation; namely, enlarging the range of compensation and establishing an essential emergency fund. From the perspective of protecting the rights of the victims of oil pollution damage and safeguarding the public interests of the ocean, this study puts forward relevant legal suggestions, which are expected to make valuable contributions to improving the compensation system for oil pollution damage caused by ships in China and promoting the governance of the marine environment.

Effects of different particle-sized insoluble dietary fibre from citrus peel on adsorption and activity inhibition of pancreatic lipase - Ben Yu; Qingmiao Tang; Caixia Fu; Joe Regenstein; Junyi Huang; Lufeng Wang (Food Chemistry, 2023)

What Do We Need to Do? The Sustainable Development of Chinese Marine Fisheries: A Legal Perspective - Ben-Chao Fu; Hao Liu (Fishes, 2022)
Both the nation with rich marine fishery resources and the nation importing marine fishery resources are increasingly attending to the sustainable growth of marine biodiversity and the balanced governance of fisheries. Nevertheless, Chinese marine fisheries have achieved progressively sustainable development from a legal perspective. Initially, the present paper outlines the legal relationship between sustainable development theory and marine fisheries, discusses the current circumstances of Chinese marine fisheries, and reviews Chinese legal regimens governing marine fisheries. Given this context, the paper explores and analyzes the legal issues (legislation, law enforcement, and administrative management) concerning the sustainable development of Chinese marine fisheries. These significant matters are then discussed to advance a potential approach to enhancing the legal systems governing Chinese marine fisheries and ameliorating the sustainable development of such fisheries. The results will serve as a reference to help lawmakers, decision-makers, and practitioners.

Model test of a geogrid-reinforced tailing accumulation dam - Changbo Du; Ben Niu; Fu Yi; Lidong Liang (Bulletin of Engineering Geology and the Environment, 2022)

Unification and Coordination of Maritime Jurisdiction: Providing a Judicial Guarantee for International Trade and Marine Transport - Ben-Chao Fu (Frontiers in Marine Science, 2022)
Maritime jurisdiction plays an important role in international trade and marine transport. It involves special kinds of rules that vary among different countries and legal systems. Thus, in international maritime jurisdiction, the coordination and settlements of jurisdictional conflicts are vital for the uniformity of international maritime law. This study provides a comparative analysis of maritime jurisdiction in international trade and marine transport. First, it introduces the concept, category, and legal characteristics of maritime jurisdiction based on historical sources. Then, we conduct a comparative analysis of the civil law system, common law system, international conventions, and Chinese maritime jurisdiction provisions, focusing on their differences and the existing legal problems. Among other suggestions for the improvement of the rules of maritime jurisdiction, this study proposes the unification and coordination of maritime jurisdiction, which could impact international trade and marine transport.

Viscoelastic-plastic constitutive model for the creep and stress relaxation characteristics of a geogrid - Changbo Du; Ben Niu; Fu Yi; Lidong Liang (Arabian Journal of Geosciences, 2022)

Chemical constituents from the barks of Melia azedarach and their PTP1B inhibitory activity - Sheng-Nan Zhang; Lin Huang; Rui-Jing Ma; Mei-Feng Yang; Ben-Fu Wei; Hong-Zhi Song; Heng-Shan Wang; Qin-Gang Tan (Natural Product Research, 2021)

Application of multi-component joint inversion in oil and gas exploration: A case study of reservoir and gas saturation prediction of the Xujiahe formation in the PLN area of the central Sichuan Basin - Dong Wang; Zhen-Hua He; Xu-Ben Wang; Le Li; Hai-Tao Yang; Zhi-Guo Fu; Hong-Yan Wang (Applied Geophysics, 2020)

Numerical study on the climatic effect of the lake clusters over Tibetan Plateau in summer - Yang Wu; Anning Huang; Ben Yang; Guangtao Dong; Lijuan Wen; Lazhu; Zhiqi Zhang; Zhipeng Fu; Xueyan Zhu; Xindan Zhang; Shuxin Cai (Climate Dynamics, 2019)

The China Multi-Model Ensemble Prediction System and Its Application to Flood-Season Prediction in 2018 - Hong-Li Ren; Yujie Wu; Qing Bao; Jiehua Ma; Changzheng Liu; Jianghua Wan; Qiaoping Li; Xiaofei Wu; Ying Liu; Ben Tian; Joshua-Xiouhua Fu; Jianqi Sun (Journal of Meteorological Research, 2019)

PAXX Participates in Base Excision Repair via Interacting with Pol β and Contributes to TMZ Resistance in Glioma Cells - Ben Yang; Xueqi Fu; Jilong Hao; Jing Sun; Zongzhu Li; Haisong Li; Haiyang Xu (Journal of Molecular Neuroscience, 2018)

Temperature-related mortality impacts under and beyond Paris Agreement climate change scenarios - Ana Maria Vicedo-Cabrera; Yuming Guo; Francesco Sera; Veronika Huber; Carl-Friedrich Schleussner; Dann Mitchell; Shilu Tong; Micheline de Sousa Zanotti Staglior Coelho; Paulo Hilario Nascimento Saldiva; Eric Lavigne; Patricia Matus Correa; Nicolas Valdes Ortega; et al. (Climatic Change, 2018)

Synthesis and bioactivity evaluation of novel azoles containing dithiocarbamate moieties - Ben Fu; Maocheng Wu; Lu Huang; Qiuye Wu; Shudong Wang; Xiaoyun Chai (Medicinal Chemistry Research, 2017)

Long-Term Generation Scheduling of Hydropower System Using Multi-Core Parallelization of Particle Swarm Optimization - Sheng-li Liao; Ben-xi Liu; Chun-tian Cheng; Zhi-fu Li; Xin-yu Wu (Water Resources Management, 2017)

Oroxylin A inhibits H 2 O 2 -induced oxidative stress in PC12 cells - Qinghe Han; Haiyu Wang; Chong Xiao; Ben-Dong Fu; Chong-Tao Du (Natural Product Research, 2017)

Subinhibitory concentrations of phloretin repress the virulence of Salmonella typhimurium and protect against Salmonella typhimurium infection - Wu Shuai-Cheng; Fu Ben-Dong; Chu Xiu-Ling; Su Jian-Qing; Fu Yun-Xing; Cui Zhen-Qiang; Xu Dao-Xiu; Wu Zong-Mei (Antonie van Leeuwenhoek, 2016)

Pharmacokinetics, Antitumor and Cardioprotective Effects of Liposome-Encapsulated Phenylaminoethyl Selenide in Human Prostate Cancer Rodent Models - Jeong Yeon Kang; Mathew Eggert; Shravanthi Mouli; Ibrahim Aljuffali; Xiaoyu Fu; Ben Nie; Amy Sheil; Kendall Waddey; Charlie D. Oldham; Sheldon W. May; Rajesh Amin; Robert D. Arnold (Pharmaceutical Research, 2015)

Review of melting experiments on carbonated eclogite and peridotite: insights into mantle metasomatism - Peng-Fei Zhang; Yan-Jie Tang; Yan Hu; Hong-Fu Zhang; Ben-Xun Su; Yan Xiao; M. Santosh (International Geology Review, 2012)

Sprout vacuum-infiltration: a simple and efficient agroinoculation method for virus-induced gene silencing in diverse solanaceous species - Hua-xue Yan; Da-qi Fu; Ben-zhong Zhu; Hai-ping Liu; Xiao-ying Shen; Yun-bo Luo (Plant Cell Reports, 2012)

Breakdown of orthopyroxene contributing to melt pockets in mantle peridotite xenoliths from the Western Qinling, central China: constraints from in situ LA-ICP-MS mineral analyses - Ben-Xun Su; Hong-Fu Zhang; Yue-Heng Yang; Patrick Asamoah Sakyi; Ji-Feng Ying; Yan-Jie Tang (Mineralogy and Petrology, 2012)

Association between ATM 5557G>A polymorphism and breast cancer risk: a meta-analysis - Chen Mao; Vincent C. H. Chung; Ben-Fu He; Rong-Cheng Luo; Jin-Ling Tang (Molecular Biology Reports, 2012)

The origin of spongy texture in minerals of mantle xenoliths from the Western Qinling, central China - Ben-Xun Su; Hong-Fu Zhang; Patrick Asamoah Sakyi; Yue-Heng Yang; Ji-Feng Ying; Yan-Jie Tang; Ke-Zhang Qin; Yan Xiao; Xin-Miao Zhao; Qian Mao; Yu-Guang Ma (Contributions to Mineralogy and Petrology, 2011)

Bats aloft: variability in echolocation call structure at high altitudes - Erin H. Gillam; Gary F. McCracken; John K. Westbrook; Ya-Fu Lee; Michael L. Jensen; Ben B. Balsley (Behavioral Ecology and Sociobiology, 2009)

Development and characterization of a new 1BL.1RS translocation line with resistance to stripe rust and powdery mildew of wheat - Tian-Heng Ren; Zu-Jun Yang; Ben-Ju Yan; Huai-Qiong Zhang; Shu-Lan Fu; Zheng-Long Ren (Euphytica, 2009)

Incidental discovery of high systemic lupus erythematosus disease activity associated with cytomegalovirus viral activity - Ben Yu-Jih Su; Cheng-Yu Su; Shan-Fu Yu; Chung-Jen Chen (Medical Microbiology and Immunology, 2007)

A method for lake ecosystem health assessment: an Ecological Modeling Method (EMM) and its application - Fu-Liu Xu; Richard W. Dawson; Shu Tao; Jun Cao; Ben-Gang Li (Hydrobiologia, 2001)